2023
DOI: 10.21009/biosferjpb.26765
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between metacognitive awareness and cognitive learning outcomes based on gender of biology education students

Romi Adiansyah,
Astuti Muh. Amin,
Ahmad Yani
et al.

Abstract: Metacognitive awareness has a significant and complex correlation with cognitive learning outcomes. So far, there have not been many studies investigating the correlation between metacognitive awareness and cognitive learning outcomes based on gender. This research aimed at determining the correlation between metacognitive awareness and cognitive learning outcomes based on the gender of biology education students. The samples of this research were biology education students in the third semester of 2020/2021 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…However, the results are inconsistent with findings that indicated female learners underperform compared to their male counterparts, even when conditions are seemingly equivalent [ 49 ]. Furthermore, studies that established that female learners thrive more than male learners when learner-centred methods are utilized while male learners succeed in comparison to female learners when taught using a teacher-centred method have been contradicted [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results are inconsistent with findings that indicated female learners underperform compared to their male counterparts, even when conditions are seemingly equivalent [ 49 ]. Furthermore, studies that established that female learners thrive more than male learners when learner-centred methods are utilized while male learners succeed in comparison to female learners when taught using a teacher-centred method have been contradicted [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, some researchers have reported contradictory findings, indicating no significant disparities in learning outcomes between males and females in liberal arts (humanities) and social sciences where CRE is situated [ 55 ]. Furthermore, it is argued that when learner-centred teaching methods are utilized instead of teacher-centred approaches, female learners tend to exhibit superior learning outcomes compared to male learners [ 56 , 57 ]. The use of appropriate instructional methods can serve as a source of motivation during instruction [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students with critical thinking are more capable of making informed judgments in their daily lives, thus enhancing their capabilities to communicate and present efficiently (Saad et al, 2024). Individuals often exhibit a proclivity for selecting specific learning strategies in order to effectively accomplish learning objectives (Adiansyah et al, 2023). Based on the results of preliminary observations on junior and senior high school biology teachers in Ternate City, it was found that the learning process was still teacher-centered, which made the students less active in learning and less active to interact with other students'.…”
Section: Introductionmentioning
confidence: 99%